Purines in Parkinson's: from epidemiology of caffeine and urate to therapeutics - Schwarzschild, Michael (Henry Stewart Talks, 2014)
Purines in Parkinson's: from epidemiology of caffeine and urate to therapeutics, Purines as PD protectants, Purines & Parkinson’s, Pursuing Epi clues to protection for Parkinson’s, Coffee, tea and the risk of PD, Caffeine consumption and a reduced risk of PD: Possible explanations for this inverse association – Caffeine, post-menopausal estrogen and risk of Parkinson’s disease, Caffeine targets in humans, CSC reverses MPTP neurotoxicity, Adenosine A2A receptor KO mimics caffeine’s protective effect in the MPTP model of PD, Potential benefits of A2AR blockade in PD, Caffeine and A2A receptors in models of PD, Brain distribution of adenosine receptors, Brain distribution of adenosine receptors, Industry A2A antagonists advancing to clinical trials for PD, Caffeine consumption & the risk of dyskinesia in PD, Urate oxidase mutations during primate evolution, Advantage of higher urate?, Epidemiology of urate and PD, Serum urate predicts progression of Parkinson’s disease, higher urate predicts a slower rate of PD progression, Functional imaging can identify dopaminergic deficits of PD, Higher serum urate at baseline predicts a slower rate of losing DA transporter binding sites in PD, CSF and serum urate as predictors of progression of Parkinson’s disease, Is urate a predictor of slower progression in other neurodegenerative diseases?, Urate prevents dopaminergic neuron death in primary cultures of midbrain neurons, Astrocytes potentiate the neuroprotective effects of inosine and urate, Urate prevents MPP+-induced dopaminergic neuron degeneration, SURE-PD study, UpUrS-PD study